2002
DOI: 10.1258/09564620260216290
|View full text |Cite
|
Sign up to set email alerts
|

HIV post-exposure prophylaxis after sexual assault: the experience of a sexual assault service in London

Abstract: Compared with other published studies the completion rate of HIV-PEP in our study was high. The uptake and adverse events of HAART in this scenario were similar to previously published studies. A multidisciplinary approach to the management of this patient group will improve adherence to PEP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 9 publications
0
23
0
1
Order By: Relevance
“…4 Our data confirm findings of previous studies reporting a low likelihood of follow-up and completion of nPEP treatment in victims of SA, with followup rates ranging from 38% to 53%, and completion rates ranging from 11% to 63%. [18][19][20]24 In fact, the completion rate of health care workers who begin nPEP (a highly motivated and knowledgeable group of patients) is in the vicinity of 30%, although they are more likely to be given a three-drug regimen that carries with it a higher likelihood of adverse reactions. 25 Although our overall completion rate was 21%, the completion rate of those patients started on nPEP from the HIV clinic was 100%, whereas only 18% of those patients who were started from the ED completed the 30-day regimen.…”
Section: Discussionmentioning
confidence: 99%
“…4 Our data confirm findings of previous studies reporting a low likelihood of follow-up and completion of nPEP treatment in victims of SA, with followup rates ranging from 38% to 53%, and completion rates ranging from 11% to 63%. [18][19][20]24 In fact, the completion rate of health care workers who begin nPEP (a highly motivated and knowledgeable group of patients) is in the vicinity of 30%, although they are more likely to be given a three-drug regimen that carries with it a higher likelihood of adverse reactions. 25 Although our overall completion rate was 21%, the completion rate of those patients started on nPEP from the HIV clinic was 100%, whereas only 18% of those patients who were started from the ED completed the 30-day regimen.…”
Section: Discussionmentioning
confidence: 99%
“…5 One hundred and fifty patients attended the service during the twelve months of the study. The patients were assessed for HIV PEP and ten were considered eligible for treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Acceptance by 20-60% of patients offered nPEP was found in three additional single-site studies (Diniz, Almeida, Ribeiro, & Macedo, 2007;Reeves, Jawad, & Welch, 2004;Wiebe, Comay, McGregor, & Ducceschi, 2000). And acceptance greater than 80% was found in the remaining four studies; two conducted at single sites (Garcia et al, 2005;Limb, Kawsar, & Forster, 2002), one inclusive of city-wide data (Sonder et al, 2007), and one regional (Carrieri, Bendiane, Moatti, & Rey, 2006).…”
Section: Npep Acceptancementioning
confidence: 98%
“…Four studies reported the frequency of baseline HIV testing (Bechtel, Ryan, & Gallagher, 2008;Campbell et al, 2006;Merchant, Phillips, Delong, Mayer, & (2007) 172 - Garcia et al (2005) 347 278 (80%) Kerr et al (2003) 676 - Limb et al (2002) 150 10 (6%) Reeves et al (2004) 92 - Rey et al (2008) 98 -Sonder et al (2007) 29 - Templeton et al (2005) 146 117 (80%) Wiebe et al (2000) 258 -Studies with US populations conducted pre-CDC guidelines Linden et al (2005) 181 167 (92%) Merchant et al (2008) 780 610 (78%) Merchant et al (2003) 461 286 (62%) Moe and Grau (2001) 58 48 (82%) Myles et al (2000) 376 354 (94%) Pesola et al (1999) 27 - Straight and Heaton (2007) 179,149 -Note: *The percentage reflects the number of patients eligible out of the total sample size. Becker, 2008;Straight & Heaton, 2007).…”
Section: Hiv Baseline Testingmentioning
confidence: 99%